Multi-Criteria Decision Analysis in Land Suitability and Land Use Planning, Kadawedduwa Watershed, Nilwala River Basin, Sri Lanka - Keerthirathna, H.G.U.; Stimers, M.J.; Lenagala, S.K. (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2019)
The aim of this study is to determine physical land suitability for agriculture, residential and industrial land uses using by Multi-Criteria Decision Analysis (MCDA) and GIS approaches and to compare present land use versus potential land use. Presently, many development projects and decision makers face problems in land use planning and management, including allocation of limited unutilized land among various stakeholders, and lack of sufficient environmental policies for sustainable use. Degradation of these areas has caused increasing concern among managers, and revealed the importance of land suitability analysis. A broad range of criteria is required for performing effective land suitability selection, and MCDA is an appropriate method to handle such heterogeneous criteria. This research examines a relatively new method of multi-criteria evaluation by using a spatial analytical hierarchy method for determining the most suitable land uses for the Nilwala River Basin, Kadawedduwa Watershed, in southern Sri Lanka.